2020
DOI: 10.1177/1941738120949181
|View full text |Cite
|
Sign up to set email alerts
|

Energy Drinks and Their Adverse Health Effects: A Systematic Review and Meta-analysis

Abstract: Context: Energy drinks are the fastest growing product in the beverage industry. However, there is concern regarding potential for adverse effects with use. Objective: To evaluate the reported adverse effects of energy drink consumption. Data Sources: The electronic databases MEDLINE, EMBASE, and PubMed were searched for relevant studies from inception to November 2019, and pertinent data were abstracted. Study Selection: Only clinical studies reporting adverse events after energy drink consumption were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 47 publications
3
44
0
3
Order By: Relevance
“…6 Moreover, most ED consumers, either males (78%) or females (63%), were consuming ED daily or several times weekly, possibly increasing the risk of getting caffeine toxicity, thus potentiating its side effects. [43][44][45][46][47] Our results showed that 22.2% of refugee schoolchildren were overweight, and 24.6% were obese, indicating that refugee adolescents are more likely to develop diseases associated with obesity, such as metabolic diseases and heart diseases. 48 The overall prevalence of MetS in refugee schoolchildren based on IDF criteria was high (6.3%) and significantly higher among obese (21.5%) than overweight (5.2%) with no gender differences.…”
Section: Discussionmentioning
confidence: 65%
“…6 Moreover, most ED consumers, either males (78%) or females (63%), were consuming ED daily or several times weekly, possibly increasing the risk of getting caffeine toxicity, thus potentiating its side effects. [43][44][45][46][47] Our results showed that 22.2% of refugee schoolchildren were overweight, and 24.6% were obese, indicating that refugee adolescents are more likely to develop diseases associated with obesity, such as metabolic diseases and heart diseases. 48 The overall prevalence of MetS in refugee schoolchildren based on IDF criteria was high (6.3%) and significantly higher among obese (21.5%) than overweight (5.2%) with no gender differences.…”
Section: Discussionmentioning
confidence: 65%
“…A meta-analysis of 96,549 participants demonstrated that the most frequent reported adverse events among pediatric patients were insomnia (35.4%), stress (35.4%), and depressive mood (23.1%), whilst among adult population, the most reported adverse effects were restlessness/jitteriness/shaking hands (29.8%), insomnia (24.7%), and gastrointestinal upset (21.6%). For both groups, the most common side effects for the particular systems were tachycardia for the cardiorespiratory system, headaches for the neurological system, insomnia/sleeping-related symptoms for the psychological system, and increased urination for the renal system [ 60 ]. Since mild adverse effects may be acceptable to the ED users, severe complications are unwanted.…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…In addition, dehydration was pointed out as a patomechanism of exercise-induced asthma because a reduced airway surface protects against further liquid loss [ 73 ]. As shaking hands is the one of the most common side effects [ 60 ], it may exert a negative effect on the final outcome in sport disciplines where precision is required. On the other hand, a study where an association between ED consumption and mental problems was investigated presented that young people who ingested EDs and were engaged in physical activity reported less symptoms of depression [ 75 ].…”
Section: Alarming Effects Associated With Energy Drink Consumptionmentioning
confidence: 99%
“…Obesity and hyperinsulinemia have been reported as metabolic adverse effects [22]. Neuropsychiatric adverse effects include epileptic seizures [13,14,24,32,37,40,41], reversible cerebral vasoconstriction [22], intracerebral haemorrhage [13,22], acute psychosis [13,22,37], and risk-taking behaviours [13] (for instance, hazardous driving with excessive speed and seat belt omission [22], sexual risk taking [22], and drug use [41]).…”
Section: Caffeinementioning
confidence: 99%
“…Furthermore, several studies suggest that EDs may serve as a gateway to other forms of substance dependence [16,22,23]. Additionally, an association with suicide plan/attempt in a paediatric population with a frequent use of EDs (≥5 times/week) has been described [24].…”
Section: Introductionmentioning
confidence: 99%